1965
DOI: 10.1113/jphysiol.1965.sp007541
|View full text |Cite
|
Sign up to set email alerts
|

Continuous radiotelemetric records of the deep body temperature of some unrestrained African mammals under near‐natural conditions

Abstract: The deep body temperatures of a wide range of animals have been recorded in the literature. The majority of these records has depended upon discrete measurements made while the animal was captive and restrained, or immediately after death by shooting. Estimates of the variation in deep body temperature have been achieved by making a series of measurements of rectal temperature of one animal at different times of the day, or by making a series of single measurements on several animals immediately upon captivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
3

Year Published

1965
1965
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 6 publications
6
25
3
Order By: Relevance
“…Our results confirm previous demonstrations of robust daily rhythmicity of core body temperature in camels (Bligh and Harthoorn, 1965;Bouâouda et al, 2014;El-Allali et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results confirm previous demonstrations of robust daily rhythmicity of core body temperature in camels (Bligh and Harthoorn, 1965;Bouâouda et al, 2014;El-Allali et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The lower temperature in the study by Bligh and Harthoorn (1965) can be explained by the fact that they measured body temperature in the camel's hump, whereas Bouâouda et al (2014) The robustness of the core body temperature rhythm was between 40 and 80%, depending on whether it was calculated for individual animals or for the group as a whole, which is consistent with the findings in sheep, goats, horses, and cattle (Piccione et al, 2003). When the animals were maintained in a stable environment (without a light-dark cycle or a cycle of ambient temperature), core body temperature still exhibited near-24-hour rhythmicity, thus confirming the endogenous nature of the rhythm previously documented in a large number of species (Refinetti, 2010), including the camel (El-Allali et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…If this generality is accepted, then the thermoregulatory performance of the sheep under field conditions is unexceptional. However, a recent comparative study ofthe nychthemeral variation of body temperature of some mammals in East Africa (Bligh & Harthoorn, 1964) has indicated that there are species-specific differences in the degree of thermostability of mammals. In that study, where nychthemeral variations of up to 30 C were recorded in some species, the sheep was found to be the most thermostable.…”
Section: Discussionmentioning
confidence: 99%